Development of gluten-free breads started with chia and flaxseed sourdoughs fermented by selected lactic acid bacteria - Dentice Maidana, Stefania (2020)
Gluten-free baked goods are a challenge for biotechnologists and nutritionists because their low baking characteristics. Lactic acid bacteria (LAB) were identified and characterized from chia flour and spontaneously fermented sourdough. Based on techno-functional and safety properties, Weissella cibaria CH28 together with Lactobacillus plantarum FUA3171 and Lactobacillus fermentum FUA3165 from fermented sorghum, were used as inoculants to ferment chia and flaxseed sourdoughs used for sorghum gluten-free breadmaking. Compared to chemically acidified control, fermentation products present in oilseed sourdoughs after 24 h showed a marked increase of lactate, xylose, arabinose, free amino acids and hydrogen peroxide while glucose was undetectable. Sorghum-based laboratory breads manufactured with different percentages (0–40% w/w) of oilseeds sourdoughs fermented by W. cibaria CH28 and lactobacilli showed that those started with 30 and 40% of sourdoughs significantly improved specific volume and visual appearance compared to 100% sorghum breads. Sensory evaluation of gluten-free sorghum breads showed 40% of replacement as the most accepted by panelists who were also able to discriminate breads inoculated with fermented and unfermented chia dough. The use of chia sourdoughs fermented with selected autochthonous LAB strains as ingredient for gluten-free breadmaking, will have an impact in baked foods functionality and healthiness.